2361. Factors Associated With Sepsis Development in Cellulitis. A Prospective Analysis of 606 Episodes in Adult Patients. (26th November 2018) - Collazos, Julio; Fuente, Belen De La; Garcia, Alicia; Gomez, Helena; Menendez, Candela; Enriquez, Hector; Sanchez, Paula; Alonso, Maria; Guerra, Jose; Artero, Arturo; Blanes, Marino; Fuente, Javier De La; et al.
Abstract: Background: Cellulitis, a frequent cause of admission of adult patients to medical wards, occasionally evolves to sepsis. In this study, we analyze the factors related to sepsis development. Methods: Prospective and observational study of 606 adult patients with cellulitis admitted to several Spanish hospitals. Comorbidities, microbiological, clinical, laboratory, diagnostic, and treatment data were analyzed. Sepsis was diagnosed according to the criteria of the 2016 International Sepsis Definitions Conference. Multiple logistic regression modeling was performed to determine the variables independently associated with sepsis development. Results: Mean age was 63.4 years and 51.8% were men. Overall 65 (10.7%) patients developed sepsis, 7 (10.8%) of whom died, but only 4 (6.2%) due to cellulitis. Drawing of blood ( P < 0.0001) or any ( P < 0.0001) culture, and identification of the agent ( P = 0.005) were more likely among septic patients. Septics had also a longer duration of symptoms ( P = 0.04), higher temperature ( P = 0.03), more extensive cellulitis ( P = 0.02), higher leukocyte ( P < 0.0001) and neutrophil ( P < 0.0001) counts, serum creatinine ( P = 0.001), and CRP ( P = 0.008) than non-septics. Regarding therapy, septic patients were more likely to undergo changes in the initial antimicrobial regimen ( P < 0.0001), received more antimicrobials ( P < 0.0001), were intravenously treated for longer ( P = 0.03), and underwent surgery more commonly ( P = 0.01) than non-septics. Death ( P = 0.002), leukocyte counts ( P = 0.002), serum creatinine ( P = 0.003), drawing of blood cultures ( P = 0.004), change of the initial antimicrobial regimen ( P = 0.007) and length of cellulitis ( P = 0.009) were independently associated with sepsis development in the multivariate analysis. The area under the ROC curve of a formula derived from blood leukocytes and serum creatinine for predicting sepsis development was 0.732 (95% CI 0.659–0.805), P < 0.0001, and its most discriminant cutoff value had a sensitivity 67.7% and specificity 74.4% for this purpose. Conclusion: Death, increased blood leukocytes and serum creatinine, blood culture drawn, modification of the initial antimicrobial regimen, and maximum length of cellulitis were associated with sepsis development in cellulitis patients. Disclosures: All authors: No reported disclosures.